Public Space, Community, and Enjoyment in Music Festival: The experiences of 2019 Jazz Traffic Festival audience in Surabaya - Karyasih Marga; Ratih Puspa (Airlangga University, 2021)
This research focuses on the visitors' experience of the Jazz Traffic Festival (JTF) 2019 in Surabaya. This research then aims to know how the experience gained by the visitors in JTF with the genre expansion was incorporated despite its title as Jazz music Performances. This research uses case study method and descriptive-qualitative approach. The data in this research is obtained by observation and independent-interviews with four informants as visitors of JTF. The results of this study showed that each JTF visitors have a different experience due to the preference and purpose of attending the festival. JTF becomes a public space for visitors who are part of the urban community for several reasons. The visitors attend JTF for the entertainment, to escape from the routine, to build social interactions, and to actualize self-identity. in addition, the innovative effort of JTF in maintaining its existence by expanding to non-jazz music and market was apparently still enjoyed by the visitors.